Probing the activity and stability of MoO2 surface nanorod arrays for hydrogen evolution in an anion exchange membrane multi-cell water electrolysis stack. Issue 11 (23rd February 2023) - Bartoli, Francesco; Capozzoli, Laura; Peruzzolo, Tailor; Marelli, Marcello; Evangelisti, Claudio; Bouzek, Karel; Hnát, Jaromir; Serrano, Giulia; Poggini, Lorenzo; Stojanovski, Kevin; Briega-Martos, Valentín; Cherevko, Serhiy; et al.
Abstract : An active and stable hydrogen evolution electrocatalyst composed of MoO2 surface nanorod arrays was prepared using high-temperature reductive annealing. Electrodes with an area of 78.5 cm 2 were evaluated in a three-cell AEM electrolyser stack. Abstract : The development of sustainable electrocatalysts is essential for promoting anion exchange membrane water electrolysis (AEMWE) technology. Ni–Mo and MoO2 materials have enhanced alkaline hydrogen evolution reaction (HER) activity. This study investigates an active HER catalyst synthesized from MoNiO4 nano-rod arrays on nickel foam using high-temperature reductive annealing. Complete characterization of the nanostructure by SEM, HR-TEM and XPS indicates that during synthesis the crystalline MoNiO4 structure of individual rods segregates a surface enriched polycrystalline MoO2 layer rather than a Ni4 Mo alloy as reported previously. Mo and Ni electrochemical dissolution was studied by the scanning flow cell technique coupled with inductively coupled plasma mass spectrometry (SFC-ICP-MS). It was found that only Mo undergoes detectable dissolution phenomena, with the MoO2 /Ni cathode prepared at 600 °C being the most stable. Tests in an AEMWE with a Ni foam anode demonstrate a current density of 0.55 A cm −2 (2 V) at 60 °C and H2 production was stable for more than 300 h (0.5 A cm −2 ). The synthesis procedure was scaled up to prepare electrodes with an area of 78.5 cm 2 that were employed and evaluated in a three-cell AEM electrolyser stack.